2019
DOI: 10.1111/eth.12962
|View full text |Cite
|
Sign up to set email alerts
|

Reduced geographic variation in roars in different habitats rejects the acoustic adaptation hypothesis in the black‐and‐gold howler monkey (Alouatta caraya)

Abstract: Vocalizations used for long‐range communication must disperse without significant structural changes to be decoded by receivers. The acoustic adaptation hypothesis (AAH) holds that, since acoustic signals are influenced by the habitat in which they disperse, sounds will possess specific structural characteristics to diminish sound degradation. Additionally, vocalizations can also be influenced by genetics, anatomy, and/or cultural aspects. Here, we tested the AAH through quantitative comparisons of roars in fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…In this sense, reliable long-term monitoring methods would be a useful tool for scientists and wildlife managers aiming to monitor the BGHM as well as other primates. The utterance of loud calls with little variability, even among regions (Holzmann & Areta, 2020), suggests that automated signal recognition should be a reliable tool for monitoring the BGHM (Heinicke et al, 2015). Indeed, a previous assessment using automated detection of the calls of the Mantled Howler Monkey (Alouatta palliata) showed that the species was automatically detected in 35 of the 43 recordings (81.3%) in which it was present (Aide et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, reliable long-term monitoring methods would be a useful tool for scientists and wildlife managers aiming to monitor the BGHM as well as other primates. The utterance of loud calls with little variability, even among regions (Holzmann & Areta, 2020), suggests that automated signal recognition should be a reliable tool for monitoring the BGHM (Heinicke et al, 2015). Indeed, a previous assessment using automated detection of the calls of the Mantled Howler Monkey (Alouatta palliata) showed that the species was automatically detected in 35 of the 43 recordings (81.3%) in which it was present (Aide et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Our recall rate refers to the percentage of recordings that the species was automatically detected, while previous studies of primates used number of calls.Although this precludes us from making direct comparisons, our findings, together with those obtained byAide et al (2013), provide strong evidence of the effectiveness of automated signal recognition software for detecting the presence of howler monkeys. The effectiveness of automated software for monitoring howler monkeys might be partly explained by the long and loud calls of the genus (da Cunha et al, 2015), as well as limited variability of calls among populations(Holzmann & Areta 2020). Indeed, the few instances when the BGHM was detected by the observer but not by Kaleidoscope Pro, in our study, were cases in which the species was presumably calling at long distances from the recorder, according to the low sound pressure level of these calls detected in the spectrograms (Cristian Pérez-Granados personal observation).…”
mentioning
confidence: 99%